El humanismo en la educación médica - Oseguera Rodríguez, Jorge Francisco (2012)
For the last thirty years, medical science has a growing attention regarding an emphasis to return to the humanism to counteract the “corporativism” around the health care system, because it seems the main responsible of the dehumanization of the health are provided. Like medical educators, we are worried about the impact that our own professional behavior exerts on the development of the humanistic attitudes and behaviors of the medical students and residents, however it still seems that the concept “humanism” is confusing among the medical areas. This brings out the need to clarify what we understand by “medical humanism”, to reach a general agreement that supports the evaluation of the humanistic medical attitudes and behaviors and outlines specific pedagogical strategies that enhance and strengthen the term in the environment of medical education ad practice. This paper review the classical term “humanism” and its evolution inside the medical science until it may be considered as a way of life with an emphasis made on human welfare and it enables the construction of human values and norms.